"This is the best game!": Rejecting and redefining arcade norms in Bee and PuppyCat - Moran, Jacqueline (Eludamos: Journal for Computer Game Culture, 2025)
This article analyses The Best Game, a fictional arcade game encountered in the YouTube animated series Bee and PuppyCat. Although arcade games in North America have long been conceptualised as sites of masculine skill-based competition and mastery, this reputation obfuscates the diverse history of arcade games and reinforces capitalist design conventions. The Best Game offers a critique of these assumptions. By examining this fictional game through arcade history, masculinity, capitalism, and dance, this article explores how The Best Game eschews design conventions to align with the show’s mahō shōjo-inspired themes and leverages its fictionality to suggest a game that neither trains nor evaluates its players, although the result expresses resentment more than it incites resistance.